Massie : a Clique novel - Harrison, Lisi. (New York : Little, Brown and Co., 2008)
When Massie is kicked out of her exclusive riding camp and her parents insist that she get a summer job, she becomes the highest-selling Be Pretty Cosmetics girl ever by ignoring the company's philosophy.
Keywords: Sales personnel -- Fiction; Cosmetics -- Fiction; Beauty, Personal -- Fiction; Self esteem -- Fiction; Conduct of life -- Fiction; Cliques (Sociology) -- Fiction; Southampton (N.Y.) -- Fiction